From burden to balance: The role of age and education level in the distribution of refugees in Europe - Florian W. Bartholomae; Chang-woon Nam; Alina M. Schoenberg (EconPol Forum, 2025)
Migration poses both an opportunity and a challenge for the EU, as it offers a solution to labor shortages and demographic imbalances, but also creates social and economic pressure. A fairer distribution of refugees among EU member states, considering age and education level, can optimize labor markets, promote social cohesion, and reduce populist sentiment. Current models for refugee distribution often fail to align with host countries' needs, and incorporating nuanced indicators like age, education level, and social resistance can improve fairness and efficiency. Tailored policies that address integration barriers, such as skill recognition and language training, can maximize refugees' contributions to host economies and counter negative public perceptions. While giving preference to younger and educated refugees can improve integration outcomes, this approach must be reconciled with humanitarian principles to uphold ethical standards in refugee policy.
Keywords: 330